From David Ananun’s Letters - Hakobyan, Vahagn (History and Culture, 2021)
The letters published in this article are part of an extensive correspondence of the well-known Social Democrat, Marxist historian and publicist David Ananun (1880-1943). They were specially selected to clarify the nature of his relationship with the famous historian, statesman, Secretary of the Central Committee of the Communist (Bolshevik) Part of Soviet Armenia in 1922-1927, Ashot Hovhannisyan (1886-1972). At the same time, these letters show the influence of these relations on the fate of D. Ananun.The presented letters contain interesting information about the interpersonal relations between D. Ananun and A. Hovhannisyan, and also contribute to the expansion of our understanding of the social and political life of the 1910-1920s in Armenia and the Caucasus.
Keywords: David Ananun; Ashot Hovhannisyan; Karen Mikaelyan; Nikoghayos Ter-Manvelyan; friendship; specifics